Coexistence of Sjögren's syndrome and bilateral ranulas: A case report and review of the literature. Issue 2 (15th September 2021) - Koma, Yoshiro; Fujimoto, Takehiro; Sakai, Kiyoshi; Sugimura, Yukiko; Yamaguchi, Satoshi; Hibi, Hideharu
Abstract: Sjögren's syndrome and ranulas are relatively frequently occurring diseases. However, when they occur simultaneously, its clinical features and pathogenesis remain unclear. Here, we report a patient with bilateral ranulas. Magnetic resonance imaging at diagnosis revealed a "salt and pepper" appearance in bilateral parotid glands, leading a diagnosis of asymptomatic Sjögren's syndrome. She was successfully treated with excision of the left sublingual gland and sclerotherapy. A literature review suggests that this coexistence may not be very rare. In addition, it may be characterized by a high prevalence of bilateral ranulas.